Instituto AMMA Psique e Negritude - Racismo: por uma psicanálise atenta - Silva, Maria Lúcia da; Martins, Marilza de Souza; Faustino, Deivison Mendes (Percurso, 2019)
Realização: Ana Claudia Patitucci, Bela M. Sister, Cristina Parada Franch, Danielle Melanie Breyton, Deborah Joan Cardoso e Silvio Hotimsky Colaboração: Noemi Moritz Kon Participação especial: Kairú NKosi